BUILDING CHARACTER THROUGH THE TAHFIDZ PROGRAM IN SD IT AR-RAHMAN - Imam Tabroni; Cici Supiah; M. Amirudin; Siti Patimah (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of study to determine how the implementation of character education through the tahfidz in SD IT Ar-Rahman Purwakarta. This study uses descriptive qualitative methods with data collection techniques through interviews, observations, and documentation. The data analysis technique in this research in through data reduction, data presentation and data verification. The result of the study illustrates that: 1) The implementation of character education through the tahfidz program is carried out through exemplary principles through the drill method (repetition of readings), through habituation, through motivation, and good communication. 2) The forms of character developed tn the tahfidz program through the materials and methods of the tahfidz program in growing students awareness of the umportance of reading, memorizing, and practicing the Al-Qur'an in life. The obstacles faced by teachers in implementing character education include the lack of parental roles in monitoring the development of students and the lack of effectivenes in learning the tahfidz program. While the effort to overcome the obstacles and by teachers in implementing education is to provide motivation. Application of various methods and make student “Linking Book” effective.